Interpreting the Themes of Spirituality among Health Care Workers in Thailand - Yoelao, Dusadee; Mohan, Kanu Priya (The Journal of Behavioral Science, 2020)
Spirituality, as a concept and its positive consequences, is being increasingly explored in research from the viewpoint of various professional groups. An important perspective is that of the health care providers, who play an important role in any society as they take care of the health problems and the needs of the sick. Working in this profession requires a spirit of empathy and selflessness while providing service, and often stirs the spiritual component within the service provider. This paper is a part of an extensive research project initiated in by a non government organization to investigate the concept of spirituality, its causes and consequences from the perspective of health care workers in Thailand. A research sample of fifty persons was selected to be representative of all the four regions of Thailand. Qualitative techniques were used to research and analyze the meaning, causes and consequences of spirituality. The findings of this research showed that the participants from the health care services shared five themes representing the core of spirituality which were related to the: goal and meaning of life, consciousness of death, insight into self, insight into others, and non material value.